Accounting Principles In Islam: Reflections On Surah Al-Baqarah Verse 282 - A’yuni, Ika Khuril; Wahyudi, Amin (AL-WIJDÃN Journal of Islamic Education Studies, 2024)
The accounting principles in Islam play a significant role in financial management, reflecting the values of religion, ethics, and Islamic law. One of the verses that embodies these principles is verse 282 of Surah Al-Baqarah. This research explores and analyzes the accounting principles contained in verse 282 of Surah Al-Baqarah within the context of Islamic finance. Another objective is to examine the practical implications of these principles in the modern accounting context. This study employs a literature analysis method involving the study of verse 282 of Surah Al-Baqarah and literature related to accounting principles in Islam. A theoretical approach is used to correlate these principles with modern accounting concepts. The analysis of verse 282 of Surah Al-Baqarah reveals accounting principles encompassing accountability, justice, and truthfulness. These principles guide how financial recording and reporting should be conducted in Islam. The practical implications of these principles include establishing a transparent, fair economic environment based on Islamic principles in the context of modern accounting.   Keywords: Principles, Islamic Accounting